2015
DOI: 10.1371/journal.pone.0132627
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection Triggers the Secretion of the PPARγ Agonists 15-Hydroxyeicosatetraenoic Acid (15-HETE) and 13-Hydroxyoctadecadienoic Acid (13-HODE) in Human Cytotrophoblasts and Placental Cultures

Abstract: IntroductionCongenital infection by human cytomegalovirus (HCMV) is a leading cause of congenital abnormalities of the central nervous system. Placenta infection by HCMV allows for viral spread to fetus and may result in intrauterine growth restriction, preeclampsia-like symptoms, or miscarriages. We previously reported that HCMV activates peroxisome proliferator-activated receptor gamma (PPARγ) for its own replication in cytotrophoblasts. Here, we investigated the molecular bases of PPARγ activation in infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Interestingly, during HCMV virion assembly, cellular cPLA2 is packaged into the viral particle and remains within the tegument of the virions, as an “onboarded” cell-derived cPLA2 which is required for infectivity [ 23 ]. It has been shown that this cell-derived cPLA2 can be inhibited by treatment of the viral inoculum by the specific cPLA 2 inhibitor methyl arachidonyl fluorophosphonate (MAFP) before infection [ 23 , 24 ]. Accordingly, we observed that treatment of the inoculum by 50 μM MAFP abolished IE expression in NSCs ( Fig 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, during HCMV virion assembly, cellular cPLA2 is packaged into the viral particle and remains within the tegument of the virions, as an “onboarded” cell-derived cPLA2 which is required for infectivity [ 23 ]. It has been shown that this cell-derived cPLA2 can be inhibited by treatment of the viral inoculum by the specific cPLA 2 inhibitor methyl arachidonyl fluorophosphonate (MAFP) before infection [ 23 , 24 ]. Accordingly, we observed that treatment of the inoculum by 50 μM MAFP abolished IE expression in NSCs ( Fig 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that 13-HODE and 15-HETE were the PPARγ agonists secreted by cytotrophoblasts and placenta explants infected by HCMV. In this case, however, no 9-HODE changes were detected [ 24 ]. This suggests tissue specificity in the response to HCMV infection with regard to fatty acids metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistence of a moderate to large ductus arteriosus following birth is a risk factor for BPD. Furthermore, the previously mentioned hydroxy acids and ketones are associated with placental signaling via activation of peroxisome proliferator-activated receptor (PPAR)␥ (10,35,61). Specifically, 9-and 13-HODE, and 13-oxo-ODE are putative ligands of PPAR␥, the expression of which, in the placenta, has been shown to be vital for proper cardiac tissue development (3) and implicated in the regulation of PH development (55).…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, we had previously showed that PPARg activity is mandatory for HCMV replication and is dramatically enhanced in cytotrophoblasts and placentae infected by HCMV. 20 Therefore, we investigated the outcomes of HCMV infection on PPARg in NSCs.…”
Section: Role Of Pparg In Hcmv Neuropathymentioning
confidence: 99%